143 A pivotal role for NRF2 in endothelial detachment–implications for endothelial erosion of stenotic plaques. (May 2019) - Satta, Sandro; McElroy, Michael; Langford-Smith, Alex; Ferris, glenn; Teasdale, Jack; Kim, Yongcheol; Niccoli, Giampaolo; Tanjeko, Ajime; Serré, Jef; Hazell, Georgina; Sala-Newby, Graciela; Wang, Ping; et al.
Abstract : Introduction: Endothelial erosion of atherosclerotic plaques and resulting thrombosis causes approximately 30% of acute coronary syndromes (ACS). Plaque erosion is most frequently observed in smokers, which induces endothelial dysfunction, partially through elevated circulating mediators of inflammation, such as tumour necrosis factor-alpha (TNFα), as well as free radical, oxidative and chemically induced damage. We have previously demonstrated that fresh aqueous cigarette smoke extract (CSE) increases the expression of Nrf2-target genes in human coronary artery endothelial cells, which was further increased by TNFα in a shear stress-dependent manner. Methods: The haemodynamic environment significantly regulates both plaque development and endothelial function, therefore we determined the haemodynamic environment permissive for plaque erosion. We reconstructed the coronary artery geometries from 17 heart attack patients with thrombi overlying intact fibrous caps (OCT-defined erosion) and performed computational fluid dynamic analysis. We created an in vitro model of erosion by culturing human coronary artery endothelial cells under elevated flow and exposing them to CSE and TNFα. Results: We identified that in 14 cases of OCT-defined erosion occurred in areas of stenosis, with the preeminent flow feature being elevated flow. Exposing human coronary artery endothelial cells to elevated flow, CSE and TNFα induced significant endothelial detachment, which was enhanced by pharmacological activation of the antioxidant system controlled by transcription factor Nrf2. The Oxidative Stress Growth INhibitor genes OSGIN1 and OSGIN2 were both maximally upregulated under these conditions and also in the aortas of mice exposed to cigarette smoke. Adenoviral overexpression of OSGIN1+2 in static culture resulted in cell cycle arrest in S-phase (5.5-fold increase, p= 0.003), with a significant increase in the number of multinucleated cells (4.5-fold, p= <0.001). Immunocytochemical analysis indicated loss of focal adhesions and stress fibres, dysregulation of autophagy and induction of senescence in HCAEC, with a significant increase in senescence-associated β-galactosidase staining (6.7-fold, p= <0.001) and P16 expression (3.2-fold, p= 0.035). Importantly, overexpression of either Nrf2, or OSGIN1+2 induced cell detachment, which was independent of apoptosis, and could be rescued by inhibition of HSP70 nucleotide binding site using VER-155008, or AMPK activation using Metformin. Conclusions: In summary, we have defined the haemodynamic environment in which endothelial erosion occurs and identified that smoking-induced hyperactivation of Nrf2 may promote endothelial cell detachment, contributing to plaque erosion overlying stenotic plaques, through the combined upregulation of OSGIN1 and OSGIN2. This highlights a completely novel mechanism potentially contributing to 30% of ACS and suggests possible therapeutic avenues for further investigation. Conflict of Interest: none